2010
DOI: 10.4314/ajcem.v11i3.57765
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and prevalence of <i>Mycobacterium tuberculosis</i> complex amongst people living with HIV in Osun state, Nigeria.

Abstract: Human immunodeficiency virus (HIV) infection has created a special niche for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…PCR to detect the presence or absence of IS6110 of M. tuberculosis complex DNA was carried out as described previously[ 4 9 ] was used for molecular detection of M. tuberculosis complex from clinical samples. After processing of sample using USP technology, 2 μl of the processed sample was added to the 18 μl PCR master mix containing Taq polymerase and IS6110F (cctgcgagcgtaggcgtcgg) and IS6110B (ctcgtccagcgccgcttcgg) primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR to detect the presence or absence of IS6110 of M. tuberculosis complex DNA was carried out as described previously[ 4 9 ] was used for molecular detection of M. tuberculosis complex from clinical samples. After processing of sample using USP technology, 2 μl of the processed sample was added to the 18 μl PCR master mix containing Taq polymerase and IS6110F (cctgcgagcgtaggcgtcgg) and IS6110B (ctcgtccagcgccgcttcgg) primers.…”
Section: Methodsmentioning
confidence: 99%
“…Immunochromatographic technique for identification of M. tuberculosis complex from broth culture of mycobacteria has also joined methods for rapid diagnosis of TB[ 8 ]. We have recently shown that the identification of M. tuberculosis complex from culture using PCR[ 9 ] can reduce the time it takes for identification in this environment but this has not reduced the time it takes for culturing the aetiological agent from clinical samples. It is on the premise that we evaluated the detection of M. tuberculosis complex from clinical samples by PCR in order to determine the suitability of the test in our environment.…”
Section: Introductionmentioning
confidence: 99%
“…In another similar study, the prevalence of M. tuberculosis in people living with HIV in Osun state of Nigeria was found to be 25% using microscopy, 15% and 18.75% for M. tuberculosis and M. tuberculosis complex, respectively, suggesting there is overestimation of TB cases using microscopy. A positive association with occupation involving was also highlighted acquisition of M. avium complex infection [20].…”
Section: Tuberculosismentioning
confidence: 97%
“…In smears stained with carbol fuschin or auramine and examined under the light microscope, the tubercle bacilli typically appear as straight or slightly curved rods but depending on growth conditions and age of the culture, bacilli may vary in size and shape from short coccobacilli to long rods. The dimensions of the bacilli have been reported to be 1-10µm in length (usually 3-5µm), and 0.2-0.6 µm in width (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium tuberculosis forms a complex that comprises members implicated in human tuberculosis. (10) while M. canetti is a rare MTBC strain which produces smooth and glossy colonies, with all cases so far isolated from people who have been to the horn of Africa (5,11); M. pinnipedii has been shown to be responsible for TB in marine host while M. caprae is responsible for TB in goats and M. microti infects larger mammals. Mycobacterium tuberculosis as the predominant cause of human TB is the most successful of human bacterial pathogens, and is sometimes referred to as Koch's bacillus after the discoverer (12).…”
Section: Introductionmentioning
confidence: 99%